GLOBAL CITIZENSHIP EDUCATION: PARENTS’ REFLECTIONS - Žegunienė, Vaida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The paper aims to contribute to the understanding of the concept global citizenship education. Global citizenship education is defined as democratic and sustainable education that pursues to educate a global citizen who is able to perceive the processes of the modern society, to demonstrate a positive attitude and to adapt to the global environment.It is emphasised that global citizenship is a factor ensuring development of a global citizen and his/her functioning within the global context. The analysis of the European and Lithuanian documents revealed that global citizenship education has to be initiated at the pre-primary school because children aged 5- to 7-years are capable to form/construct new global skills. Thus, to have global citizenship education integrated into the pre-primary school education is a must, but still gaps and obstacles exist.The objectives of the research are to investigate how the parents of pre-primary school aged children perceive the concept global citizenship. Data for this research were collected using the qualitative method - an interview. A major advantage of an interview is that this method allows to investigate parents' individual perception of global citizenship education.The most interesting aspect of the data gathered is that parents do not demonstrate complete understanding of global citizenship education and majority of them are not completely familiar with this phenomenon. They relate global citizenship education to travelling and living abroad, to knowledge of other countries/cultures and specific social issues such as pollution, discrimination, poverty.  Taking into consideration the complexity of this process the parents’ perception is insufficient. Therefore, further study has to be initiated regarding teachers’ attitude to initiation and implementation of global citizenship education into the curriculum of the pre-primary school.